Non parametric estimation for fractional diffusion processes with random effects. Issue 4 (4th July 2019) - El Omari, Mohamed; El Maroufy, Hamid; Fuchs, Christiane
ABSTRACT: We propose a nonparametric estimation for a class of fractional stochastic differential equations (FSDE) with random effects. We precisely consider general linear fractional stochastic differential equations with drift depending on random effects and non-random diffusion. We build ordinary kernel estimators and histogram estimators and study their L p risk ( p = 1 or 2 ), when H > 1 / 2 . Asymptotic results are evaluated as both T = T ( N ) and N tend to infinity.